All-cause mortality during the influenza season 20192020: comparison with previous influenza seasons in the territory of the local health authority “Central Tuscany”, Italy - Levi, M.; Cipriani, F.; Balzi, D. (Annali di Igiene Medicina Preventiva e di Comunità, 2025)
Introduction. Because of the 24 months latency in the release of official data on causes of death, and in consideration of the limited testing capacity during the first pandemic wave, to estimate the COVID-19related mortality in 2020, the evaluation of all-cause mortality excess is often used instead. Our study aimed at assessing whether in Central Tuscany, Italy, an excess all-cause mortality occurred in the 2019-2020 influenza season, which partly overlapped with the months of the first pandemic wave in which the impact of COVID-19 was the highest. Materials and Methods. Age- and sex-adjusted mortality rates for 2019-2020 influenza season were compared with those of influenza seasons 2009-2010 to 2016-2017. Results. No all-cause mortality excess was observed in the 2019-2020 influenza season, which, on the contrary, was characterized by the lowest all-cause mortality rate. Conclusion. Our finding can be explained by the imposition, in early March 2020, of a national lockdown, which came into effect in an early epidemic phase in Tuscany, and thus limited the transmission of SARSCoV-2 infection, as well as influenza, in the territory. In March and April, by causing the death of vulnerable elderly patients who had been spared by the mild seasonal flu in the prior months, COVID-19 acted with a harvesting effect.